In vitro phytochemical characteristics and antioxidant capacity of Aloe vera, Plukenetia volubilis, Caiophora carduifolia, Cecropia membranacea - Franco Quino, César (2016)
Introduction. Antioxidants have shown chemopreventive potential in degenerative, inflammatory, autoimmune, oncology and respiratory distress associated pathologies. Objective. To assess the phytochemical and antioxidant properties in vitro by DPPH and ABTS method. Design. Observational analytical. Location. Laboratory of Experimental Pharmacology, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological/Chemical Material. Aloe vera leaves, Plukenetia volubilis seeds, Caiophora carduifolia leaves-stalks, Cecropia membranacea leaves. Interventions. Observation and analysis of the antioxidant capacity by DPPH-method mean effective concentration (EC50) of the extracts and trolox equivalent antioxidant capacity by the ABTS method. Main outcome measures. Phytochemical preliminary march, antioxidant percent uptake inhibition by DPPH radical, determination of equivalent trolox/gextract. Results. Cecropia membranacea presented more secondary metabolites, alkaloids, saponins, flavonoid compounds; required smaller dosage to achieve the antioxidant effect (EC50 = 0.159 mg/mL) in attracting DPPH radical; achieved the best antioxidant effect by ABTS method (5.834 uM trolox/g). Caiophora carduifolia (0.87 mg/mL – 0.44 mg/mL) had trolox similar effects (p> 0.05). Aloe vera and Plukenetia volubilis also had antioxidant dose dependent effect. Conclusions. Concentration dependent in vitro antioxidant effect has been shown, higher with Cecropia membranacea and Caiophora carduifolia and lower with Aloe vera and Plukenetia volubilis.